ANALYSIS OF HEALTH STATUS OF WORKERS IN COAL INDUSTRY - M. Platikanova (Trakia Journal of Sciences)
Purpose: Assessment of the health status of working operators in the substations in the coal industry. Material and methods: Prophylactic examinations were carried out on 82 workers responsible for ensuring the security of the power supply in the mines. Some basic indicators (range of prophylactic examinations, relative share of sick persons, structure of the momentary illness) were followed. A connection has been sought between the established deviations in the health status and the working environment factors, as well as the harmful habits. Results: Diseases of the organs of the circulation (66.03%) and "Endocrine diseases" (9.43%) predominate in the registered pathology. The same share is the class "Diseases of the eye and its eye appendages” and "Diseases of the respiratory system" (5.66%). Work environment factors are not directly related to health hazards. Smoking, alcohol consumption, obesity, stress are important to unlock some diseases. Conclusions: Periodic medical examinations allow early detection of diseases and especially their timely treatment. On the basis of the health status analysis, the necessary health and medical activities, services and programs for the protection of the health of the employees can be developed, planned and implemented.